2012
DOI: 10.1002/kin.20722
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic analysis of degradation of doripenem in the solid state

Abstract: The kinetic and thermodynamic parameters of degradation of doripenem were studied using a high-performance liquid chromatography method. In dry air, the degradation of doripenem was a first-order reaction depending on the substrate concentration. At increased relative air humidity, doripenem was degraded according to the autocatalysis kinetic model. The dependence ln k = f(1/T ) was described by the equations ln k = 5.10 ± 13.06 − (7576 ± 4939)(1/T ) in dry air and ln k = 46.70 ± 22.44 − (19,959 ± 8031)(1/T ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…For oxidative media, second‐order kinetics was verified in both concentrations of the agent. In a recent work, the solid state of doripenem was investigated with a focus on stability and degradation kinetics, testing different temperatures (70–120°C) and relative humidity (0, 50, 66, 76 and 90%; Cielecka‐Piontek, Jelinska, Dolhan, & Zalewski, ). In dry air, the decomposition was a first‐order reaction depending on the substrate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…For oxidative media, second‐order kinetics was verified in both concentrations of the agent. In a recent work, the solid state of doripenem was investigated with a focus on stability and degradation kinetics, testing different temperatures (70–120°C) and relative humidity (0, 50, 66, 76 and 90%; Cielecka‐Piontek, Jelinska, Dolhan, & Zalewski, ). In dry air, the decomposition was a first‐order reaction depending on the substrate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The observed rate constants of tebipenem degradation in the solid state are listed in Table 1. It was noted that tebipenem degradation products had a catalytic effect, as was the case with other compounds containing 4:5 bicyclic fused rings (doripenem, clavulanic acid) 11,13 . In the chromatograms of degraded samples of tebipenem, decreased peaks of tebipenem were observed while no peak originating from the degradation products appeared 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies into the stability of antibiotics have reported formation of various degradation products and changes in the kinetics of degradation depending on the action of physicochemical factors [4][5][6][7] . Kinetic and thermodynamic analysis of degradation in solutions and in the solid state has been conducted for cabapenems registered for medicinal use [8][9][10][11] . To the best of our knowledge, there have been no reports on the stability of tebipenem.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic study of biapenem degradation demonstrated that the introduction of a bicyclic thiazolium moiety at C4 of bicyclic 4:5 fused rings improved the stability of biapenem in comparison with some H-and CH 3 -carbapenem analogs [5,[14][15][16]. However, the susceptibility of biapenem to degradation under the influence of stress factors applied in this work is still high and needs to be considered while selecting storage conditions for biapenem preparations and in the process of preparing infusions of those drugs.…”
Section: Discussionmentioning
confidence: 99%